Microscopic Mechanism Angle of Repose in Friable Loess and Its Relationship With Slope Angle - Dong, Haoyu; Wang, Jiading; Zhang, Dengfei; Xu, Yuanjun; Li, Zhenxiao (Frontiers in Earth Science, 2022)
The angle of repose in soil particles plays a key role in slope stability. There was a need for investigation on the association between the angle of repose in loess particles and the angel of slopes. The fixed funnel methods with different particle sizes were carried out. The pressure of particle gravity weight was obtained based on the vibration stacking test. Four contact structures in loess particles were put forward including triangular pyramid contact structure (TS), rectangular pyramid contact structure (RS), pentagonal pyramid contact structure (PS) and hexagon contact structure (HS). The particles transformed successively in four kinds of contact structures. The transformation of entropy value of the particles in different accumulation areas was discussed during the process of accumulation. The relationship between the natural angle of repose and the evolution of the contact structures was established. Combined with the existing experimental conclusion that loess particles transform in four stable states in turn, the reason that the friction angle of uniform sand particles proposed by Shields in 1936 is 33° was explained. The formation theory of loess angle of repose was well-extended to speculate the formation process of the loess slope system. It is verified that loess slopes were mainly distributed under 30°.